2016
DOI: 10.1038/srep37964
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Host Characteristics of Recent and Established HIV-1 Infections in Kisumu based on a Multiassay Approach

Abstract: Integrated approaches provide better understanding of HIV/AIDS epidemics. We optimised a multiassay algorithm (MAA) and assessed HIV incidence, correlates of recent infections, viral diversity, plus transmission clusters among participants screened for Kisumu Incidence Cohort Study (KICoS1) (2007–2009). We performed BED-CEIA, Limiting antigen (LAg) avidity, Biorad avidity, and viral load (VL) tests on HIV-positive samples. Genotypic analyses focused on HIV-1 pol gene. Correlates of testing recent by MAA were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…Overall, our data also confirm that the HIV-1 MSM epidemic from Coastal Kenya is largely characterized by a predominance of sub-subtype A1 infections, which is consistent with subtype diversity literature from Kenya [1318]. However, and while some studies have also reported high and/or increasing circulating or complex recombinant forms amongst the general heterosexual population [1922], this was not evident in our study population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our data also confirm that the HIV-1 MSM epidemic from Coastal Kenya is largely characterized by a predominance of sub-subtype A1 infections, which is consistent with subtype diversity literature from Kenya [1318]. However, and while some studies have also reported high and/or increasing circulating or complex recombinant forms amongst the general heterosexual population [1922], this was not evident in our study population.…”
Section: Discussionsupporting
confidence: 91%
“…In Kenya, several studies have described HIV-1 subtype distribution in the general heterosexual population, and reported a predominance of HIV-1 sub-subtype A1 [1318], with increasing inter-subtype recombinants [1922]. In addition, a study amongst the heterosexual population from Coastal Kenya reported minimum clustering and high genetic variability between the study-volunteers’ pol sequences [21].…”
Section: Introductionmentioning
confidence: 99%
“…When clinical information is combined with the recency assay to classify recent HIV infection, FRR has been shown to be reduced. According to WHO guidelines, we used CD4+ T cell count <200 cells/ml, and VL <1000 copies/mL as reclassification criteria for recent infection to reduce misclassification (Aghaizu et al, 2014;Laeyendecker et al, 2018;Otecko et al, 2016;Shah et al, 2017). A previous study showed that FRR was reduced from 4.9% to 0.4% when VL was incorporated into an algorithm initially consisting of the recency assay and CD4+ T cell count.…”
Section: Discussionmentioning
confidence: 99%
“…Another study done on the gag and env regions of HIV-1 in 74 samples revealed A1, C, D, G, A1/C, A1/D, C/A1, D/A1, A1/A2 and A2/C [ 21 ]. In Kisumu, analysis of 100 samples identified the following subtypes; A, D, C, G, AD, AC, AG [ 22 ]. In Nairobi A1, D, C, G, AD, AC, AG and A2D were identified in analysis of 140 samples [ 23 ].…”
Section: Introductionmentioning
confidence: 99%